Indigenous peoples and the confrontation of Covid-19 in Brazil: the role of the Supreme Court (Research, Society and Development, 2022)
Objective: to investigate the performance of the Federal Supreme Court (STF), in the context of the Covid-19 pandemic, in defense of the right to health of indigenous peoples. Methodology: through jurisprudential, legislative and bibliographic research, from March 2020 to June 2022, an important decision was identified within the scope of the Supreme Court, on the subject discussed here. This is ADPF nº 709, proposed by the association “Articulation of the Indigenous Peoples of Brazil” (APIB) and six political parties, judged on 8-5-2020. Result: In this claim, the Court partially granted the request to extend assistance from the Health Care Subsystem for Indigenous Peoples (SasiSUS) to all Brazilian indigenous people. It determined that SasiSUS would serve all indigenous people in tribal villages, regardless of the situation in their territories. According to the Rapporteur, being indigenous is a matter of identity and does not require any action on the part of the Union to legalize or recognize its territory, as underlined by ILO Convention 169. Final considerations: the performance of the Supreme Court was positive. Controversial decisions were made. And, precisely because of the controversial nature of some decisions, a polarized opinion was formed in Brazil between those who defend the performance of court ministers and those who repudiate it, accusing them of acting outside the Constitution.